2003
DOI: 10.1002/adem.200310405
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Magnesium Corrosion—A Framework for Improved Alloy Performance

Abstract: The purpose of this paper is to provide a succinct but nevertheless complete mechanistic overview of the various types of magnesium corrosion. The understanding of the corrosion processes of magnesium alloys builds upon our understanding of the corrosion of pure magnesium. This provides an understanding of the types of corrosion exhibited by magnesium alloys, and also of the environmental factors of most importance. This deep understanding is required as a foundation if we are to produce magnesium alloys much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
1,105
2
17

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,820 publications
(1,152 citation statements)
references
References 56 publications
28
1,105
2
17
Order By: Relevance
“…In fact, the intrinsic galvanic cell (macrogalvanic and microgalvanic effects from the gold coating and impurities of the Mg particles, respectively) serves to further increase the anodic dissolution of Mg, assisting in the pitting corrosion. 27 Thus, the rapidly evolving hydrogen bubbles at the Mg surface provide the thrust essential for the directional propulsion of the Janus micromotors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the intrinsic galvanic cell (macrogalvanic and microgalvanic effects from the gold coating and impurities of the Mg particles, respectively) serves to further increase the anodic dissolution of Mg, assisting in the pitting corrosion. 27 Thus, the rapidly evolving hydrogen bubbles at the Mg surface provide the thrust essential for the directional propulsion of the Janus micromotors.…”
mentioning
confidence: 99%
“…Even faster Mg dissolutions and propulsions were observed in strongly acidic environments (pH < 2), while strongly alkaline media (pH > 12) resulted in nearly complete hindrance of the Mg-water reaction. 27 Adding 0.1 mM EDTA to the natural seawater resulted in a decreased speed (to 40 mm s À1 ), possibly due to chelation of Mg + ions, and hence hindrance of the hydrogen evolution reaction (eqn (2)). …”
mentioning
confidence: 99%
“…A similar occurrence was observed for η-Al 8 Mn 5 particles in 1 M NaOH; this was followed by the formation of pits around these particles [36]. It has been shown that β-Mg 17 Al 12 plays a dual role in the corrosion resistance of AZ91 alloy [24][25][26]32]. Indeed, it can act as either a barrier or a galvanic cathode: as mentioned above, the corrosion potential of β-Mg 17 Al 12 has been found to be more positive than that of the α-magnesium phase (matrix), which may therefore accelerate the galvanic corrosion of α-magnesium [21].…”
Section: Introductionmentioning
confidence: 57%
“…Corrosion of Mg alloys is typically faster than the corrosion of high-purity Mg in simple chloride solutions, because the second phase in the Mg alloy causes microgalvanic acceleration of the corrosion of the alpha-Mg matrix [22,[54][55][56]. This micro-galvanic corrosion acceleration typically occurs preferentially next to the second phase, and is often wrongly characterised as pitting corrosion.…”
Section: Magnesium Corrosion Assessmentmentioning
confidence: 99%
“…Chen [20] proposed a mesh made from a Mg alloy for cranial repair, as the Mg enhances bone regrowth, and the H 2 that diffuses into the brain tissue may reduce the extent of tissue damage. However, despite the potential benefits of Mg alloys in medical applications, the key factor that must be addressed is the apparent, relatively-high corrosion rates of Mg alloys [21,22]. The tendency to corrode in the body allows Mg alloys to be used in temporary medical implants or devices.…”
Section: Medical Magnesium and Biocorrosionmentioning
confidence: 99%